La réforme québécoise des Institutions financières - Bouchard, Jean-Marie (Assurances)

(untitled) (HEC Montréal, 1985)
The profound modifications to the insurance world induced by the adoption of Bill 75, in June 1984, are not impromptu changes. Rather, they are attributable to an evolution and a modernization of Quebec's financial institutions. This evolutionary process, which began several years ago, is likely to continue over the coming months. It is this perspective of the reform that the author wishes to emphasize by underlining the recent amendments to the Law of Insurance.